Importance of Debit card with rotary quota implementation in ABC (2016)
This study that was denominated, Importance of Debit card with rotary quota implementation in ABC, it was suggested ,with a high level deepening, very significance information to the Solidary Economy organizations (Ethics Banking) which ABC belongs to and compete with the Ordinary Banking. Here , it is described ,in a clearly and simple way, different frames (Theorical, Conceptual, Lergal), Objectives , Strategic alliances, low-value payment systems (SPBV) in Solidary Economy sector , its architecture, resources and security systems which are used to access to financial world, products and services portfolio, target market , the fact of cooperative and solidary sector ( Ethics Banking) against Traditional Banking (Capitalism Economy) in Colombia, its inversion plan, benefits and social welfare. Also policy, its regulations , statute modification , agreements facing administrative council or governing board of the organization , activity timetable to Debit Card with Rotary Quota implementation project (see Figure 1) and communication or connection plan ( see Figure 2).